Wacana Intelektual Keagamaan Islam di Indonesia Bersama Timur Tengah - Irvan Mustofa Sembiring (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2021)
In this day and age, for Indonesian citizens who practice rihlah science in the Middle East, there is an assumption among some people that someone who does this rihlah will have a negative impact on Indonesia. In fact, since Islam entered the archipelago, the relationship between the archipelago and the Middle East has been established. Actually, how is the discourse of Islamic religious intellectuals in Indonesia and the Middle East?. This study uses the historical method. This research informs that first, the contact between Indonesian Islamic intellectuals and the Middle East has been going on since Islam entered the archipelago. Second, Islamic intellectuality in Indonesia is increasingly developing when the Muslims of the archipelago travel to the Middle East through the haj pilgrimage, study and settle in the Middle East, then develop it in the archipelago. Third, Islamic religious intellectuals in Indonesia who emerged after the Islamization process were Sufi schools. Fourth, then this Islamic intellectuality continues to develop which leads to fiqh such as the syafi'i school of thought, as well as the flow of faith such as ahlus sunnah wa al jamaah. Fifth, Islamic intellectuals in Indonesia entered the modern era with figures such as young people in Minangkabau such as Haji Muhammad Djamil Djambek, Haji Abdullah Ahmad, Haji Abdul Karim Amrullah and Haji Muhammad Thaib Umar, who have long been exploring knowledge in the Middle East.